An interesting case of recurrence of the gastrointestinal stromal tumor (GIST) - Godlewski, Janusz; Kuciel-Lisieska, Grażyna (Contemporary Oncology/Współczesna Onkologia, 2005)
Gastrointestinal stromal tumors, GIST, are rare tumors which have been described for about 5 years. The illness occurs in men and women equally and mostly concerns middle aged patients and older. The average age of onset is about 50-60 years. GIST is mostly located in the stomach (60-70%) and small intestine (20-30%). In 10% of patients GIST is located in other parts of the alimentary tract: esophagus, large intestine or rectum. Size of GIST ranges from a few millimeters to 30 cm in diameter. The basic method giving patients with gastrointestinal stromal tumor, GIST, a chance to be cured is the radical surgical treatment. After radical surgical operations the recurrence rate is 60-70%. 5-year survival after the operation occurs in about 35-65% of cases. The mean survival is 1 year if the tumor is inoperative or during the operation metastases are found. GIST metastasizes to the liver or results in an intraabdominal growth. This paper presents the case of a 70-year-old man with enormous abdominal tumor. Such large tumor was difficult to be removed surgically. Pressure and infiltration on liver in the postoperative time resulted in continuous bleeding from the liver surface. That is the reason why the patient was reoperated in the following days. The histopathological examination showed that large abdominal tumor was the recurrence of stomach GIST operated 8 years before.